Statistical Analysis of Cardiovascular Risk Factors and Links with Mental Health of Adolescents - Dapkutė, Ignė; Rekašius, Tomas; Simanauskas, Kazys (Lithuanian Journal of Statistics, 2016)
The paper analyses whether arterial hypertension, overweight, excessive drinking, smoking andinsufficient sports activity have an impact on the behaviour and emotional well-being of young people aged17–18. A questionnaire of Achenbach is used for investigating teenagers’ psychological difficulties. Categoricalvariables are analysed using logistic regression and log-linear models.
Keywords: behavioural and emotional difficulties; questionnaire of Achenbach; mental health; cardiovascular diseases; logistic regression; log-linear models